Isolation and identification of Brucella melitensis in goats. - Ahmed Al-Garadi, Maged; Bejo, Siti Khairani; Omar, Abdul Rahman; Zakaria , Zunita (Medwell Publishing, 2011)
Isolation of Brucella melitensis is the standard gold of identification and confirmation of animal brucellosis. However in Malaysia, Brucella sp., infection of goat was increasing recently and there is no evidence for diagnosis of the serover of Brucella sp., that cause the disease in goat population except the detection of serological methods. Isolation and identification of Brucella melitensis have been done by bacteriological methods in addition to conventional Polymerase Chain Reaction (PCR) and Real-time PCR for detection of Brucella melitensis from samples collected from vaginal swabs on suspected farm. In conclusion, four isolate have been got out of 300 vaginal samples and all isolate is belong to Brucella melitensis server 1. The Real-time PCR is the easy and save method for confirmation of brucellosis in goats population.